2021
DOI: 10.1002/smi.3089
|View full text |Cite
|
Sign up to set email alerts
|

Political affiliation dissimilarity: Exploring lone affiliate employees' work attitudes and experiences

Abstract: Political affiliation is an important demographic variable that has been relatively neglected in the organizational literature. At present, it is unclear how political dissimilarity between employees and their coworkers affects employees' attitudes and experiences, and whether traditional theories are applicable to this unique form of diversity. Based on time‐lagged data from a sample of working Americans (N = 360), we found that lone affiliates (employees who work with coworkers who do not share the same poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Considering the effort devoted to supporting diversity in organizations, the modest attention to the effects of political affiliation is surprising (Henderson & Jeong, 2022). Since many people are prejudiced against politically dissimilar others (Chambers et al, 2013), and most adults engage in daily interaction with other people at their workplace, it is important to study the consequences of political prejudice in work settings.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the effort devoted to supporting diversity in organizations, the modest attention to the effects of political affiliation is surprising (Henderson & Jeong, 2022). Since many people are prejudiced against politically dissimilar others (Chambers et al, 2013), and most adults engage in daily interaction with other people at their workplace, it is important to study the consequences of political prejudice in work settings.…”
Section: Discussionmentioning
confidence: 99%
“…In the Snihur (2021) study, evidence of negative bias was detected in conservative reviewers toward nonconservative applicants, though the same effect was not supported for liberal reviewers. In a study by Henderson and Jeong (2020), it was observed that Democrats had lower levels of job satisfaction and affective commitment when working in Republican majority institutions, but the same effect was not observed in Republicans working in Democrat majority institutions. With mixed results in workplace outcomes related to any one particular ideology, it may be important to remain skeptical of effects that have not been replicated until further research might support such findings.…”
Section: Political Ideology and Organizationsmentioning
confidence: 95%